2019
DOI: 10.3390/ijerph16214185
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Aromatherapy Combined with Music Therapy on Anxiety, Stress, and Fundamental Nursing Skills in Nursing Students: A Randomized Controlled Trial

Abstract: Purpose: Nursing students often experience anxiety and stress when taking exams that test their fundamental nursing skills. Complementary alternative methods, such as aromatherapy and music therapy, have effectively alleviated such negative emotions among nursing students. However, few studies have examined the effects of combined therapy interventions or compared the effects of different interventions. This study identified the individual and combined effects of aromatherapy and music therapy on test anxiety,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(53 citation statements)
references
References 18 publications
1
26
0
5
Order By: Relevance
“…When comparing the efficacy of aromatherapy to music, all the selected studies (Cao et al., 2016; Lehrner et al., 2005; Wang & Yang, 2014) indicated that there was no significant difference in any intergroup comparison (for any outcome) between aromatherapy and music groups. This result appeared consistent with one previous research, which found comparable effects between aromatherapy and music on anxiety, stress and skill performance among nurses who were undergoing a fundamental nursing skill performance test (Son, So, & Kim, 2019). Numerous studies have confirmed that music therapy, such as listening to calming and slow‐tempo (approximately sixty beats per minute, which is similar to the average heart rate of adult humans) music, is an effective diversion therapy to reduce anxiety and facilitate relaxation under circumstances that lead to nervousness and stress (e.g.…”
Section: Discussionsupporting
confidence: 92%
“…When comparing the efficacy of aromatherapy to music, all the selected studies (Cao et al., 2016; Lehrner et al., 2005; Wang & Yang, 2014) indicated that there was no significant difference in any intergroup comparison (for any outcome) between aromatherapy and music groups. This result appeared consistent with one previous research, which found comparable effects between aromatherapy and music on anxiety, stress and skill performance among nurses who were undergoing a fundamental nursing skill performance test (Son, So, & Kim, 2019). Numerous studies have confirmed that music therapy, such as listening to calming and slow‐tempo (approximately sixty beats per minute, which is similar to the average heart rate of adult humans) music, is an effective diversion therapy to reduce anxiety and facilitate relaxation under circumstances that lead to nervousness and stress (e.g.…”
Section: Discussionsupporting
confidence: 92%
“…Lupien et al have shown that nurses experience high levels of test anxiety, state anxiety, and stress, which can be improved after intervention [16]. Sonia et al point out that the effects of stress on the brain and behavior in adulthood are reversible and usually disappear when the stressor stops [17]. Thus, analysis of possible stressors is important to deal with the pressure of pediatric nurse.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, yoga, stretching, and physical exercise ( Auty, Cope, Liebling, 2017 ), counseling, phone consultation, referral to clinics, peer support, dialectical behaviour therapy, cognitive behavioural therapy ( Van Zyl et al, 2020 ), and the use of a buddy system ( Hall et al, 2018 ) have been shown to enhance resilience and psychological well-being. Music therapy ( Son, So, Kim, 2019 ) has demonstrated effectiveness in reducing stress, anxiety, and depression; while self-care information, tailored tools, crisis planning, and psychoeducational interventions ( Holman, Johnson, O'Connor, 2018 ) have demonstrated effectiveness in enhancing overall psychological wellbeing. Finally, sleep hygiene strategies have demonstrated effectiveness in enhancing sleep ( Espie et al, 2016 ) while virtual tours have been effective in addressing stress and psychological wellbeing ( Smith, 2019 ).…”
Section: Discussion and Limitationsmentioning
confidence: 99%